The geodynamic and tectonic evolution of the Palaeoproterozoic Sefwi Greenstone Belt, West African Craton (Ghana) - (:unkn) unknown (My University, 2018)
This thesis investigates the Palaeoproterozoic crust of the West African Craton in southwest Ghana, providing insight into its controversial geodynamic and tectonic evolution. Rocks of the study area comprise greenschist- to amphibolite facies, mafic to felsic volcanic and volcaniclastic rocks, high-grade paragneisses and low-grade volcano-sedimentary packages, all of which are extensively intruded by multiple generations of granitoids. New lithological, metamorphic and structural maps are constructed using integrated field mapping and interpretation of regional airborne geophysical datasets. This approach is used to constrain the deformation history of the sparsely exposed rocks of the NE- to NNE-striking Sefwi Greenstone Belt and the adjacent volcano-sedimentary domains deformed during the Eburnean Orogeny (2150–2070 Ma). Combined geochemical and geochronological analysis of the magmatic suites of the Sefwi Greenstone Belt reveal calc-alkaline, volcanic arc affinities, as well as a striking similarity to Neoarchean TTGs that require diverse magma sources and petrogenetic processes. Rare inherited zircon cores from the Palaeoproterozoic magmatic suite yield ages of ca. 2250 to 2270 Ma, with granitoid emplacement ages ranging between ca. 2189 and 2081 Ma. Zircon Lu-Hf analysis reveals consistently positive εHf(t) values and two-stage crustal model ages between 2650 and 2250 Ma, indicative of a radiogenic proto-crust and short crustal residence times. The magmatic evolution reveals the coeval generation of sodic, high-silica TTGs derived from partial melting of low-K mafic sources and dioritic magmas generated in a metasomatised, LILE-enriched mantle wedge at ca. 2155 Ma. Subsequent emplacement of high-K quartz monzonites at ca. 2136 Ma supports the interaction of mantle-derived magmas and remelting of existing TTGs. The final stage of magmatism is characterised by the emplacement of two-mica-granites and leucogranites along the NW margin of the Sefw
Keywords: African Research